A Study of Blackhole and Wormhole Attacks in Mobile Adhoc Networks - Tran, Hoang Hai; Nguyen, Dang Toi (Old Journal, 2020)
In the Mobile Ad-hoc Network (MANET), there are several ways of attacking network operation bypassing fault routing information between malicious and normal nodes. It will degrade efficiency of the network so we cannot archive the purposes of the designed MANET. Since it is deployed in an open network environment with characteristics of high mobility, lack of physical security and independent management, the network is vulnerable to attacks. In related works, we have seen a lot of works focusing on single type of attacks but in our paper, we study how routing attacks work and study how we can simulate combination of blackhole and wormhole attacks. Our code will be open to community so others can use to test with its security mechanism or secure routing protocols.